UV-vis spectroscopic characterization of heterocyclic azines as colorimetric chemosensors for metal ion detection - Batista, Rosa Maria Ferreira (2014)
Thienyl, pirrolyl and furyl azine derivatives L1-L3 were obtained in excellent yields (93-98%) using a simple methodology that allows their synthesis and purification in higher yields, compared to previous methods. The photophysical properties of compounds L1-L3 were studied by UV-vis spectroscopy in acetonitrile. Spectrophotometric titrations of receptors L1-L3 in the same solvent, in the presence of several cations such as Cd(II), Co(II), Cr(III), Cu(II), Fe(II), Fe(III), Hg(II), Ni(II), Pb(II), Pd(II) and Zn(II) revealed that they could be used as colorimetric chemosensors for Hg(II), Cu(II), Cr(III) and Fe(III).